NEW TRENDS OF ONLINE SHOPPING AFTER MOVEMENT CONTROL ORDER (MCO) AMID PANDEMIC COVID-19 IN MALAYSIA - Raja Nazim Abdullah; Roszi Naszariah Nasni Naseri; Siti Asma' binti Mohd Rosdi @ Mohd Rodhi; Maryam Mohd Esa; Ibiwani Alisa Hussain (International Journal of Accounting, Finance and Business, 2024)
The outbreak of the COVID-19 pandemic left great impact on innumerable aspects of daily life specifically in retail sector. Due to some restrictions imposed by government, customer behavior underwent substantial changes to purchase goods using online platform. The objective of this study is to explore the trends of online shopping change before MCO and during MCO and how it influences customers purchasing behaviour in Malaysia. The study involved 188 respondents using online survey approach to a sample of online shopping users at Klang Valley, Selangor. Analysis revealed that users spent more on online shopping during and after the MCO. These findings have some implications for businesses as changing in consumer behaviours may transform new trends on how consumer make a final purchase.